The Prevalence of the Middle Clinoid Process: A Cross-Sectional Comparative Study in Patients with and without Pathology of the Sella Turcica - Anukulsampan, Suppaluk; Tansirisithikul, Chottiwat; Sitthinamsuwan, Bunpot (Asian Journal of Neurosurgery, 2024)
Background The middle clinoid process (MCP), particularly caroticoclinoid ring (CCR) type of the MCP, is an important part of the sphenoid bone for skull base surgery. Previous studies have shown a wide range of MCP prevalence affected by various factors. However, no study has investigated the association between the MCP and the presence of sellar lesions.Objectives The main aim of this study was to evaluate the prevalence of the MCP in the Thai population and factors associated with its presence.Materials and Methods We conducted a cross-sectional study on 400 sides from 200 patients (100 with and 100 without sellar lesions) using cranial computerized tomography scans. Demographic data and MCP characteristics were collected. The association between individual variables and the presence of the MCP was determined by univariate and multivariate analysis.Results The MCP was identified in 168 of 400 sides (42%). Patients with sellar lesions had a significantly lower prevalence of the MCP compared with normal controls (29.5% versus 54.5%, p < 0.001). Of all MCP only 6% were the CCR type. Univariate and multivariate analysis showed that the absence of the sellar lesion was the only factor significantly associated with presence of the MCP (odds ratio: 2.86; 95% confidence interval: 1.90–4.32; p< 0.001).Conclusion The prevalence of the MCP was relatively high in the Thai population, while the prevalence of the CCR was relatively low compared with previous studies. The absence of sellar lesions was the only factor associated with the presence of the MCP.
Keywords: middle clinoid process; caroticoclinoid ring; prevalence; skull base surgery; cranial computerized tomography